INFLUENCE FACTORS PRENATAL ONTOGENESIS THE PHYSICAL AND PSYCHOPHYSIOLOGICAL DEVELOPMENT OF ADOLESCENTS - Наталья Николаевна Кошко; Нина Геннадьевна Блинова; Дарья Викторовна Караульнова (The Publishing House Medicine and Enlightenment, 2018)
During prenatal and early postnatal development, theorganism is most sensitive to the effects of exogenous and endogenous factors.The features of development that were formed during the period of early development under the influence of various environmental factors may persist at later stages of ontogeny. Purpose - study of the influence of prenatal and early postnatal ontogeny factors on the characteristics of the physical and psychophysiological development of adolescents. Materials and methods. The analysis of factors of prenatal and early postnatal ontogenesis, established risk factors. The features of morphofunctional and psychophysiological development of adolescents were studied taking into account the influence of prenatal and early postnatal ontogeny factors. Results. Factors of «risk» of the period of prenatal ontogeny, the result of which is preserved until adolescence, are determine. Preeclampsia and childbirth complications affect the physical development, and stress, and unhealthy working conditions of parents leads to a decrease in the level of development of psychodynamic functions teenagers. The conclusion. The influence of risk factors for prenatal and early postnatal periods of ontogenesis on physical development and psychodynamic functions teenagers.